2011
DOI: 10.1007/s10696-011-9106-3
|View full text |Cite
|
Sign up to set email alerts
|

Corridor network design in hinterland transportation systems

Abstract: In this paper the design of the service network in intermodal barge transport is studied. The network of inland barge terminals is modelled to demonstrate potential cooperations in a corridor network. Cooperation between inland terminals leads to bundling of freight flows in the hinterland of major ports. A service network design model for intermodal barge transport is developed and applied to the hinterland network of the port of Antwerp in Belgium. Selected cooperation schemes are simulated by means of a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Consolidation is a critical issue for transport actors and bundling strategies can be classified into five basic bundling types (Kreutzberger, 2010). For barge transport, bundling can be achieved through cooperation between inland terminals, which leads to aggregate flows generation (Caris et al, 2012, Konings et al, 2013. The use of freight corridors allows avoiding flow reductions over longer distances.…”
Section: Flow Management Factorsmentioning
confidence: 99%
“…Consolidation is a critical issue for transport actors and bundling strategies can be classified into five basic bundling types (Kreutzberger, 2010). For barge transport, bundling can be achieved through cooperation between inland terminals, which leads to aggregate flows generation (Caris et al, 2012, Konings et al, 2013. The use of freight corridors allows avoiding flow reductions over longer distances.…”
Section: Flow Management Factorsmentioning
confidence: 99%
“…They concluded that cooperation between inland terminals offers an opportunity to attain economies of scale, but may not be perceived as a sole solution for reducing waiting times of inland barges at sea terminals. Thus a combination of bundling measures in the port area and in the hinterland may be necessary to improve the intermodal transport chain [13]. In his article, Dr. Olivier Podevins highlighted the decisive role of terminals in the hinterland and the changing structure of the terminal network in Western and Central and Eastern Europe (CEE) based on the empirical evidence and market observations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transport demand of a client can only be fulfilled by a specific roundtrip and containers can only be transported if both the origin and destination nodes are visited (8). Constraint (9) ensures that vessel capacity is respected. Constraints (10) to (13) (14) and the start and end port of a roundtrip should be the same (15)(16)(17)(18).…”
Section: Model Formulationmentioning
confidence: 99%
“…For geographical reasons, barge transportation is mainly based on a corridor network or line bundling design: a high-density flow along a artery with short capillary services to nodes off the corridor. Caris et al [9] consider service network design for such corridor networks in barge transport. The authors study advantages of cooperation between hinterland terminals and different bundling strategies for barge transportation in the hinterland of the port of Antwerp.…”
Section: Introductionmentioning
confidence: 99%